Invasive behavior of ulcerative colitis-associated carcinoma is related to reduced expression of CD44 extracellular domain: comparison with sporadic colon carcinoma - Araki Kayo; Kikuchi Masaomi; Numata Yoshiko; Yoshida Tsutomu; Mikami Tetuo; Nakada Norihiro; Okayasu Isao (BMC, 2011)
Abstract Background To elucidate relations of invasion of ulcerative colitis (UC)-associated carcinoma with its prognosis, the characteristics of invasive fronts were analyzed in comparison with sporadic colonic carcinomas. Methods Prognoses of 15 cases of UC-associated colonic carcinoma were compared with those of sporadic colon carcinoma cases, after which 75 cases of sporadic invasive adenocarcinoma were collected. Tumor budding was examined histologically at invasive fronts using immunohistochemistry (IHC) of pancytokeratin. Expressions of beta-catenin with mutation analysis, CD44 extracellular domain, Zo-1, occludin, matrix matalloproteinase-7, laminin-5γ2, and sialyl Lewis X (LeX) were immunohistochemically evaluated. Results UC-associated carcinoma showed worse prognosis than sporadic colon carcinoma in all the cases, and exhibited a tendency to become more poorly differentiated when carcinoma invaded the submucosa or deeper layers than sporadic carcinoma. When the lesions were compared with sporadic carcinomas considering differentiation grade, reduced expression of CD44 extracellular domain in UC-associated carcinoma was apparent. Laminin-5γ2 and sialyl-LeX expression showed a lower tendency in UC-associated carcinomas than in their sporadic counterparts. There were no differences in the numbers of tumor budding foci between the two lesion types, with no apparent relation to nuclear beta-catenin levels in IHC. Conclusions UC-associated carcinoma showed poorer differentiation when the carcinoma invaded submucosa or deeper parts, which may influence the poorer prognosis. The invasive behavior of UC-associated carcinoma is more associated with CD44 cleavage than with basement membrane disruption or sialyl-Lewis-antigen alteration.